2018
DOI: 10.1175/bams-d-17-0020.1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Late Fall ENSO Teleconnection in the Euro-Atlantic Sector

Abstract: Recent studies have indicated the importance of fall climate forcings and teleconnections in influencing the climate of the northern mid- to high latitudes. Here, we present some exploratory analyses using observational data and seasonal hindcasts, with the aim of highlighting the potential of the El Niño–Southern Oscillation (ENSO) as a driver of climate variability during boreal late fall and early winter (November and December) in the North Atlantic–European sector, and motivating further research on this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 34 publications
8
59
2
Order By: Relevance
“…Finally, there may be differences in ENSO tropospheric and stratospheric teleconnections between early and late winter. Moron and Gouirand (), King et al (), and Ayarzagüena, Inseon, et al, () suggest that there exists a significantly different teleconnection of ENSO to the Europe/North Atlantic sector in November‐December versus January‐March. Herceg‐Bulić et al () find that the January‐March ENSO response over Europe is maintained by both the stratosphere and extratropical Atlantic SSTs.…”
Section: Enso Teleconnections To the Stratospherementioning
confidence: 99%
“…Finally, there may be differences in ENSO tropospheric and stratospheric teleconnections between early and late winter. Moron and Gouirand (), King et al (), and Ayarzagüena, Inseon, et al, () suggest that there exists a significantly different teleconnection of ENSO to the Europe/North Atlantic sector in November‐December versus January‐March. Herceg‐Bulić et al () find that the January‐March ENSO response over Europe is maintained by both the stratosphere and extratropical Atlantic SSTs.…”
Section: Enso Teleconnections To the Stratospherementioning
confidence: 99%
“…In January and February, a Rossby wave develops fully over the North Pacific and North America, while the signal over the North Atlantic-Europe region becomes weak and indistinct. When we perform the MCA on the individual months using reanalysis, for November the Z500 leading mode pattern is similar to the EA pattern in the North Atlantic, with weak amplitudes in the North Pacific, in agreement with King et al (2018). For December, anomalies in the extratropical Pacific strengthen and the EA weakens, and a k 5 3 wave pattern emerges.…”
Section: Conclusion and Discussionmentioning
confidence: 59%
“…The MCA Z500 pattern in this region is more related to the El Niño extratropical pattern, which has been suggested to be distinct from the PNA in both the spatial structure and probability distribution (Straus and Shukla 2002). King et al (2018) showed that the ENSO teleconnection pattern exhibits intraseasonal changes between November and the next February. In November, the teleconnection is strong over the North Atlantic and Europe, with the El Niño teleconnection resembling the positive east Atlantic (EA) teleconnection pattern.…”
Section: Conclusion and Discussionmentioning
confidence: 83%
“…; King et al . ; KNMI, ). It should be further noted that, while we only claim weak correlation between the pressure‐gradient forcing and the fog anomaly, the other studies also found only relatively weak correlations (∼0.4) between the synoptic indices and their relevant variables of interest.…”
Section: Discussionmentioning
confidence: 99%
“…; King et al . ). However, the extent to which these factors influence the occurrence of fog on interannual and spatial scales remains unclear.…”
Section: Introductionmentioning
confidence: 97%